The Tunisian experience of participatory health governance: the Societal Dialogue for Health (a qualitative study) - Hela Ben Mesmia; Dheepa Rajan; Rim Bouhafa Chtioui; Kira Koch; Imen Jaouadi; Hala Aboutaleb; Sana De Courcelles; Louisa Atmani; Blanche Pujos; Ali Mtiraoui (BMC, 2023)
Abstract Background Tunisia has been engaged in the Societal Dialogue (SD) for Health process since 2012, a participatory health governance process aimed at bringing in people's voice into health policy-making. Its first success was the recently released National Health Policy 2030. This paper aims to document the SD process and to bring out the lessons learned to inspire other countries. Methods This study was based essentially on a qualitative analysis of semi-structured interviews with citizen jury members and health experts that took place from May to September 2018. The qualitative analysis adopted an inductive-deductive approach according to a cross-matrix between the themes of the interview of the two groups of interviewees. Results The qualitative analysis of the data highlighted that the Societal Dialogue created a health democracy dynamic with inclusive dialogue spaces for the population, communities, and civil society to participate in health system design. It constituted a multi-actor and multidisciplinary coordination platform to increase consensus building among actors. Initial government support and high levels of volunteer commitment allowed the process to achieve a certain level of sustainability. However, this process faced and still faces many challenges such as overreliance on volunteers; a crisis of trust; political instability and the lack of an effective communication strategy. These challenges negatively influence the policy uptake of recommendations made by the Societal Dialogue for Health. Conclusion The Tunisian societal dialogue experience highlights both the successes and challenges of a structured participatory platform, as well as the effort and perseverance it takes to keep such a process functional and relevant. A key lesson from this study is that this model of participatory health governance eventually reaches a stage where population, community, and civil society participation needs to be more institutionalized within the government routine so that it can credibly feed into health policy review processes and inform decision-makers on a regular basis.